Ties that bind: a study of the rural informal economy in India - Sarmistha, Uma (Kansas State University, 2009)
The informal sector in India, as in other developing countries, is a source of employment and livelihoods to an overwhelmingly large proportion of workers, both in rural and urban areas. The sector is very heterogeneous and consists of both traditional and modern activities which vary widely across regions and occupations. Although the urban informal sector has been widely studied, not much work has been done on the non-agricultural rural informal sector, which has witnessed significant growth over the last several decades. The present study explores the functioning of the rural informal sector in Bihar, one of the most populous and backward states of India with a high incidence of poverty and low human development indicators. Based on case studies of two sectors – textiles and food processing – and using both quantitative and qualitative data, this study profiles the nature and characteristics of the sectors, and examines the roles of social networks and institutions in its functioning. Drawing from the economic sociology literature, it tries to understand how social networking in the rural labor market can affect economic outcomes. The findings of the study indeed show that it is difficult to explain the functioning of the rural informal sector on the basis of neo-classical economic theory. The research findings illustrate a unique kind of social networking in the rural informal sector arising from caste and religion, which can be associated with the Granovetter’s embededness theory.
Keywords: Informal economy; rural; India; embededness; Sociology, General (0626)